2021
DOI: 10.1093/hmg/ddab124
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of cardiac troponin I in the general population

Abstract: Circulating cardiac troponin proteins are associated with structural heart disease and predict incident cardiovascular disease in the general population. However, the genetic contribution to cardiac troponin I (cTnI) concentrations and its causal effect on cardiovascular phenotypes is unclear. We combine data from two large population-based studies, the Trøndelag Health Study and the Generation Scotland Scottish Family Health Study and perform a genome-wide association study of high-sensitivity cTnI concentrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 82 publications
2
16
0
Order By: Relevance
“… 38 , 39 Hence, to explore the causal effects of circulating cTnI on HF and AMI, Marta R. Moksnes et al performed a two-sample MR analysis, but no causal association was found. 16 This conclusion corroborated with the findings in the present study. Consistently, another MR study suggested that GDF-15, a stress responsive cytokine, was not causally associated with stroke risk, except a suggested relationship with CES.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 38 , 39 Hence, to explore the causal effects of circulating cTnI on HF and AMI, Marta R. Moksnes et al performed a two-sample MR analysis, but no causal association was found. 16 This conclusion corroborated with the findings in the present study. Consistently, another MR study suggested that GDF-15, a stress responsive cytokine, was not causally associated with stroke risk, except a suggested relationship with CES.…”
Section: Discussionsupporting
confidence: 93%
“…15 Genetic variants associated with circulating cTnI levels were derived from the hitherto largest GWAS meta-analysis of 48,115 individuals. 16 Twelve single-nucleotide polymorphisms (SNPs) with genome-wide significance (P < 5 × 10 −8 ) were collected. The F-statistics were estimated to identify any weak instrument bias using the formula F ¼ R 2 NÀ 2 1À R 2 , where R 2 indicates the proportion of the variance of circulating cTnI explained by the genetic instruments and N refers to the sample size.…”
Section: Data Sources and Snp Selectionmentioning
confidence: 99%
“…Instrumental variables for circulating cTnI concentrations were selected from a GWAS meta-analysis of the Trøndelag Health Study ((HUNT, n = 29,839) and the Generation Scotland Scottish Family Health Study (GS:SFHS, n = 18,276) with 48,115 European individuals. [17] This GWAS identi ed 12 genome-wide signi cant (P < 5×10 − 8 ) SNPs independently associated with cTnI concentrations (Supplementary Table 1). These 12 SNPs explained 1.2% phenotypic variation of circulating cTnI concentrations.…”
Section: Genetic Instrument For Circulating Cardiac Troponin I Concen...mentioning
confidence: 99%
“…[7,22] Because genetic variants are randomly allocated at conception and unlikely to be affected by disease in later life, MR can avoid the confounding and reverse causality in observational studies. Recently, a genome-wide association study (GWAS) has identi ed several single nucleotide polymorphisms (SNPs) that are independently associated with circulating cTnI concentrations in the general population, [17] providing potential tools for MR. In this study, we aimed to use a two-sample MR to evaluate whether genetically predicted circulating cTnI concentrations are causally associated with the risk of stroke, IS, IS subtypes (large artery stroke [LAS], small vessel stroke [SVS] and cardioembolic stroke [CES]), intracerebral hemorrhage (ICH).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike CAND1 that is ubiquitously expressed in all types of human cells, CAND2 protein is only detected in striated muscles (skeletal and cardiac) and testis [36,37,222]. While the role of CAND2 in regulating CRLs has not been well elucidated yet, population genetics and genome-wide association studies have identified CAND2 as a risk factor for multiple types of cardiovascular diseases (especially atrial fibrillation) [223][224][225][226][227][228][229]. A recent study aiming to determine the mechanism by which mTOR promotes pathological cardiac remodeling identified CAND2 as a gene significantly upregulated by mTOR in mouse cardiomyocytes, and CAND2 depletion led to decreased protein level of Grk5 and disassembly, and substrate receptor modules in CRL1 complexes are changed [201,219].…”
Section: Multifaceted Roles Of Csn In Cardiac Physiologymentioning
confidence: 99%